Customer survey analysis for design and development of golf ball retriever prototype - Ismail, Iszmir Nazmi; Azman, Nur Najwa Umirah Binti Nor; Roslin, Nursyadzatul Tasnim; Isa, M.R.; Zahari, N.M.; Abidin, S.Z.; Zuhdi, Ahmad Wafi Mahmood; Eqwan, M.R.; Mohamed, Hassan; Ramli, M.Z.; Mansor, M.H.; Syaifoelida, Fevi; et al. (2023)
This paper focuses on using customer analysis in the design and development of golf ball retriever that can be operated in the driving range. The identified problems with conventional method of retrieving the balls are the golf attendant is not able to collect the balls effectively, the number of balls collected is relatively low and the operator will experience strain in their wrists while collecting the balls with the method of scooping. Hence, the methodology and results are presented according to the customer and engineering requirements. Quality Function Deployment (QFD) method by using House of Quality (HOQ) is used to align both the customers’ and engineering requirements.